Efeito da vaporização de toras na redução dos defeitos associados a tensões de crescimento de Eucalyptus grandis - Fred Willians Calonego; Elias Taylor Durgante Severo (Ciência Florestal, 2005)
The present study was carried out to evaluate log steaming effect on the reduction of defects associated with residual growth stress of Eucalyptus grandis wood. There were used logs with diameter of 20 to <25, 25 to <30 and 30 to <35 cm, from the Horto Florestal, Manduri, São Paulo. Half of the logs was steamed during 20 hours at 90ºC of temperature and 100% of relative humidity. Subsequently, the logs were live sawn and the defects resulting from the growth stresses in logs of various diameter were measured. The results indicate that log steaming provided the release of a great part of the growth stresses, without eliminating them completely, showing, nevertheless, that this treatment is feasible and advisable for growth stress relief; the boards coming from heated logs of 20 to <25 cm presented, in general, larger defect reduction, showing that the smaller the log diameter the higher the efficiency of steam treatment at 90ºC of temperature during 20 hours.